Optimization of Speech Codecs on Set of Indicators of Quality - Bezruk, V. M. (TCSET 2010, 2010)
In article theoretical and practical features of application of methods multicriteria optimization for a choice of optimum speech codecs taking into account set of indicators of quality are considered
Keywords: optimization; indicators of quality